Analysis of temperature field of milling insert with 3D complex groove using Cellular Automata. (7th March 2008) - Tan, Guangyu; Liu, Guangjun; Li, Guanghui; Song, Hui, Yiming (Kevin) Rong
A numerical method for modelling the temperature field of milling insert with 3D complex groove is proposed based on the self-organising Cellular Automata. The self-organising local rule of Cellular Automata is derived to describe the heat transfer that affects temperature of milling insert using the finite difference theory. Consequently, a Cellular Automata model is built to predict the dynamic temperature field of the milling insert with 3D complex groove, which is also called wave-edge insert. Case studies are performed using sets of selected cutting conditions. Corresponding milling experiments and finite element analysis are also conducted to verify the simulation results of the Cellular Automata method. The comparison shows the validity and advantages of the proposed method.